Pemeriksaan GDS dan Senam Kaki bagi Penderita Diabetes Mellitus di Wilayah Desa Arang Limbung Kabupaten Kubu Raya - Lestari Makmuriana; Surtikanti; Bhakti, Wida Kuswida (Indra Institute Research & Publication, 2024)
Diabetes mellitus is a non-communicable disease that occurs in a person due to an increase in blood glucose levels due to a progressive decrease in insulin secretion due to insulin resistance. One of the complications of diabetes mellitus is a disorder or abnormality in the feet called diabetic feet. Efforts to prevent diabetes mellitus feet can be done in various ways, one of which is by taking regular examinations for diabetes mellitus, complications in the sufferer's feet and following health education about examinations and diabetes mellitus foot exercises. This activity aims to provide education about diabetes mellitus foot examinations and exercises for diabetes mellitus sufferers in Arang Limbung village, Kubu Raya district. It is hoped that the implementation of service activities in the form of health education and training on examinations and diabetic foot exercises for patients is to increase the knowledge, skills and abilities of diabetic sufferers in carrying out foot examinations and carrying out diabetic foot exercises so that they can prevent the occurrence of diabetic foot wounds which will further improve their status. The health and quality of life of the community, especially in diabetes mellitus sufferers, improves.